Reasons for Delay in Seeking Care for Tuberculosis, Republic of Armenia, 2006–2007 - Dana Schneider; Scott J. N. McNabb; Marina Safaryan; Vladimir Davidyants; Ludmila Niazyan; Sona Orbelyan (Interdisciplinary Perspectives on Infectious Diseases)
Background. Tuberculosis (TB) is a leading cause of morbidity and mortality worldwide. In Armenia, case reports of active TB increased from 590 to 1538 between 1990 and 2003. However, the TB case detection rate in Armenia in 2007 was only 51%, indicating that many cases go undetected or that suspected cases are not referred for confirmatory diagnosis. Understanding why Armenians do not seek or delay TB medical care is important to increase detection rates, improve treatment outcomes, and reduce ongoing transmission. Methods. Two hundred-forty patients hospitalized between August 2006 and September 2007 at two Armenian TB reference hospitals were interviewed about symptoms, when they sought medical attention after symptom onset, outcomes of their first medical visit, and when they began treatment after diagnosis. We used logistic regression modeling to identify reasons for delay in diagnosis. Results. Fatigue and weight loss were significantly associated with delay in seeking medical attention [aOR=2.47 (95%CI=1.15, 5.29); aOR=2.99 (95%CI=1.46, 6.14), resp.], while having night sweats protected against delay [aOR=0.48 (95%CI=0.24, 0.96)]. Believing the illness to be something other than TB was also significantly associated with delay [aOR=2.63 (95%CI=1.13, 6.12)]. Almost 20% of the 240 TB patients were neither diagnosed at their first medical visit nor referred for further evaluation. Conclusions. This study showed that raising awareness of the signs and symptoms of TB among both the public and clinical communities is urgently needed.